SP0211 PTH: Good for Bone, Bad for Cartilage?. (9th June 2015) - Orth, P.
Abstract : Parathyroid hormone (PTH) and particularly its 1-34 amino acid segment (PTH [1-34]) is involved in the regulation of calcium homeostasis, is anabolic for osteocytes and chondrocytes, and its actions are mediated via the PTH receptor (PTH1R). PTH increases bone mineral density, cortical and trabecular thickness, and bone strength, resulting in an enhanced diaphyseal and spinal fracture healing and reduced fracture risk in animal models and patients, justifying its approval for the systemic treatment of postmenopausal osteoporosis (1). However, the effect of PTH on the two major components of the osteochondral unit in diarthrodial joints, i.e. subchondral bone and articular cartilage, has only seldom been investigated to date. Data available in the literature consistently confirm the osteoanabolic potential of PTH for the cortical subchondral bone plate and the cancellous subarticular spongiosa in vivo . Besides, PTH has been shown to enhance articular cartilage repair in small animal models of focal articular cartilage defects (2) as well as in generalized osteoarthritic cartilage degeneration (3-6). Against these backgrounds, we aimed to assess the effect of daily subcutaneous injections of 10 μg PTH [1-34]/kg on the normal osteochondral unit and on osteochondral defects in the rabbit model. In both investigations, articular cartilage was evaluated by macroscopic, biochemical, histological, histomorphometrical, and immunohistochemical analyses while the subchondral bone was assessed by micro-computed tomography after 6 weeks in vivo . The correlation between PTH-induced changes in subchondral bone and articular cartilage was determined. For the normal osteochondral unit (7), PTH [1-34] induced surface irregularities and reduced matrix staining of the hyaline articular cartilage. Besides, volume, mineral density, and microarchitecture of the subarticular spongiosa were enhanced and the calcified cartilage layer was broadened following application of PTH [1-34]. Importantly, the correlation analysis revealed that such alterations of these calcified tissues accounted for the observed early osteoarthritic changes of the articular cartilage. For osteochondral defects instead (8), PTH [1-34] improved the macro- and microscopic aspect of the cartilaginous repair tissue, enhanced the thickness of the subchondral bone plate and the microarchitecture of the subarticular spongiosa, and increased PTH1R expression on chondrocytes and osteocytes. Importantly, no significant correlations were established between these coexistent processes within osteochondral defects. In conclusion, our data identify a previously undescribed mechanism by which PTH-induced alterations of the subchondral bone may provoke early osteoarthritic cartilage degeneration in the normal osteochondral unit. Despite this potential adverse reaction, PTH may simultaneously stimulate articular cartilage and subchondral bone repair in osteochondral defects - in good agreement with previous findings for chondral defects and osteoarthritis (2-6). Thus, future research is warranted to shed further light on this inconsistent effect of PTH on the intact and deteriorated osteochondral unit. References: Neer RM, et al. N Engl J Med 2001;344(19):1434-41. Chang JK, et al. Arthritis Rheum 2009;60(10):3049-60. Kudo S, et al. Osteoarthritis Cartilage 2011;19(7):886-94. Sampson ER, et al. Sci Transl Med 2011;3(101):101ra93. Bellido M, et al. Osteoarthritis Cartilage 2011;19(10):1228-36. Yan JY, et al. Osteoarthritis Cartilage 2014;22(11):1869-77. Orth P, et al. Osteoarthritis Cartilage 2014;22(6):813-21. Orth P, et al. Osteoarthritis Cartilage 2012;20(10):1161-9. Disclosure of Interest: None declared